DESCRIPTION OF THE SANITATION KARANG ASEM STASION IN BANYUWANGI 2017 - Sari, Apik Mila; Puspikawati, Septa Indra; Islamiyah, Khofifatul; Ardiasnyas, Risky Bagas; Putri, Fika Ardiana (Preventif : Jurnal Kesehatan Masyarakat, 2018)
Background & Purpose: Stations are one of the public places that have sanitation facilities and enableenvironmental pollution and diseases including diarrhea, dysentery, typhus, malaria and filiarisis. The aim offinding out the sanitation conditions at Station Karang Asem in Banyuwagi. Material and Methods: thisstudy is an observational study conducted through a sheet of instrument that has been made based onapplicable laws and interview sheets. The assessment instrument consists of 3 main variables that are used asthe foundation in the assessment including the main building variables, sanitation facilities and supportingfacilities at the station. of the 3 variables there are sub-variables and also sub-variables used as ratings.Assessment is done by looking at the total final score of the sum of 3 variable scores. Results: The totalscore of the main building variable 140 means fulfilling 100% sub-variable requirements, 77 sanitationfacilities means fulfilling 50% of the assessment requirements of sub-variables and supporting facilities 97.5means meeting the 21.5% assessment requirements of sub-variables. The total score of Karang Asem stationsanitation is so that station x sanitation is 314.5. Which means in the Good category. Conclusion: KarangAsem Station in Banyuwangi has a Good category in station sanitation assessments, although there stillneeds to be an increase especially in its sanitation facilities.Keywords: station, sanitation, public place.